Analysis of Nursing Clinical Practice with Chest Physiotherapy Innovation Intervention and Pronation Position on Airway Clearance in Pediatric Patients with Pneumonia in The Keruing Room - Sriwidiastuti, Elysa; Prasetyana, Ely; Krisneki, Ice; Kartini, Kartini; Bulan, Magdalena; Rahman, Gajali; Andraini, Rus; Mari’pi, Farida (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: Pneumonia is also known as "the forgotten killer of children". Based on the 2018 Riskesdas report, the age prevalence of pneumonia among children aged 1-5 years was 2.1%. The prevalence of pneumonia in toddlers and children based on gender characteristics was (2.1%) in males and (2.0%) in females. After observations and interviews in the Keruing room of Harapan Insan Sendawar Hospital, it was found that the innovative intervention of chest physiotherapy and pronation position to improve airway clearance in pediatric patients with pneumonia had never been carried out. Objective: The purpose of KIAN is to analyze the intervention of providing chest physiotherapy actions and pronation positions on improving airway clearance in pneumonia patients in the Keruing room. Methods: Sampling in this KIAN was selected according to the inclusion criteria desired by the researcher with a total sample size of five pneumonia clients. Results and Discussion: From the results of the study, it was found that the provision of chest physiotherapy and a pronated position had changes in secretion production, breath sounds, oxygen saturation (SPO2), pulse and respiratory frequency (RR) in the five patients. So that the intervention of chest physiotherapy innovation and a pronated position is very effective in dealing with airway cleansing in pediatric pneumonia patients. Conclusion: Chest physiotherapy intervention and pronation position can reduce secretion production and increase SPO2 in paediatric pneumonia patients